Developing English Wipe and Clean Workbook Integrated Madurese Culture to Teach Language Skills and Promote Green Skills for Elementary School Students - Fijriyah, Izzah; Adinanda, Andika (Lafadz Jaya Publisher, 2023)
The objective of this research is creating innovative teaching materials, the Wipe and Clean Workbook, which has been infused with Madurese culture. This product is a reusable workbook that allows elementary school students to reinforce English skills contextually and reuse the product to minimize paper consumption. The need to give young students contextual language learning experiences and to inculcate a sense of environmental responsibility is growing as the globe faces environmental concerns. Most researches in the field of language learning and environmental education tend to focus on these aspects separately, neglecting the potential synergies that can be achieved by combining them. This research is development research using 4D development model which has 4 stages, they are Define, Design, Development, and Dissemination. Based on the percentage validation results, product developed obtains a valid category. In addition, based on the results of student questionnaire with an interpretation of score based on the Linkert scale as a whole, a percentage value of 85% is obtained in the very good category. In conclusion, the findings of this research demonstrate promising results in empowering students to become well-rounded, culturally aware, and environmentally conscious global citizens. However, further research is needed to explore the long-term impact and scalability of this product.